Harmony of Progress: Investigating Discipline, Motivation, and Learning Achievement in Citizen Education - Maman Maman; Nurul Ocktaviani; Sylvester Chisebe; Mohammed Al-Ghzewat (Journal of Social Knowledge Education (JSKE), 2024)
Research objectives: This research aims to determine: 1) the relationship between student discipline and learning achievement in Civics subjects, 2) the relationship between learning motivation and learning achievement in Civics subjects and 3) the relationship between student discipline and learning motivation and learning achievement in Civics subjects Methodology: This research is ex-post facto research and correlation research using a quantitative approach. The population in this study were students in grades VII and VIII of MTs Al Mu'minien, MTs Lohbener, MTs Ma'arif Langut and MTs Al Ghifari, totaling 1,294 students. The sampling technique used multi stage sampling with Isaac and Michael tables, and the sample obtained was 224 students. The data collection method uses a questionnaire for student discipline variables as well as learning motivation and documentation variables . Main Findings: The main finding of this research is the positive and significant relationship between student discipline and learning motivation together on civic education learning achievement. This can have the implication that with student discipline and learning motivation in students together, students' Civics learning achievement will also increase . So that it can give rise to an urge for interest in learning to achieve a goal, for example becoming class champion . Novelty / Originality of this research: The novelty of this research is the importance of the relationship between discipline and learning motivation together on student learning achievement in Citizen Education. It is considered important to combine the relationship between discipline and student learning motivation because this can be one way for students to have high levels concern for learning so that students can get good grades.